Transcranial magnetic stimulation (TMS)/repetitive TMS in mild cognitive impairment and Alzheimer's disease. (8th February 2014) - Nardone, R.; Tezzon, F.; Höller, Y.; Golaszewski, S.; Trinka, E.; Brigo, F.
<x xml:space="preserve">Abstract</x> Several Transcranial Magnetic Stimulation (TMS) techniques can be applied to noninvasively measure cortical excitability and brain plasticity in humans. TMS has been used to assess neuroplastic changes in Alzheimer's disease (AD), corroborating findings that cortical physiology is altered in AD due to the underlying neurodegenerative process. In fact, many TMS studies have provided physiological evidence of abnormalities in cortical excitability, connectivity, and plasticity in patients with AD. Moreover, the combination of TMS with other neurophysiological techniques, such as high‐density electroencephalography (EEG), makes it possible to study local and network cortical plasticity directly. Interestingly, several TMS studies revealed abnormalities in patients with early AD and even with mild cognitive impairment (MCI), thus enabling early identification of subjects in whom the cholinergic degeneration has occurred. Furthermore, TMS can influence brain function if delivered repetitively; repetitive TMS (rTMS) is capable of modulating cortical excitability and inducing long‐lasting neuroplastic changes. Preliminary findings have suggested that rTMS can enhance performances on several cognitive functions impaired in AD and MCI. However, further well‐controlled studies with appropriate methodology in larger patient cohorts are needed to replicate and extend the initial findings. The purpose of this paper was to provide an updated and comprehensive systematic review of the studies that have employed TMS/rTMS in patients with MCI and AD.